Kerangka Konseptual Teori Determinisme Teknologi - Jehalut, Ferdinandus (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
This article explains the conceptual framework of technological determinism theory. The rapid development oftechnology in the last few decades has revived the classic controversy about the relationship between technologyand society. One of the positions defended in the controversy is technological determinism. Through a qualitativeapproach and literature study methods and descriptive analysis, this theory is reviewed in this article. The data inthis study was obtained from national and international books and journals. This study found that technologicaldeterminism theory was only discovered in the 20th century. This theory believes that technology is an independententity that influences the transformation of society. However, by constructivists, this belief is consideredahistorical, reductionist and simplistic. The theory of technological determinism also turns out to have severalvariants, namely hard technological determinism and soft technological determinism. The two variants emergedas a result of different emphasis on the degree of influence of technology on society. Different interpretations oftechnological determinism have also emerged. The three interpretations are normative, nomological, andunintended consequences interpretations. Finally, the author suggests the need for a balanced reading of therelationship between technology and society. Future research needs to critically examine and question the claimsof technological determinism.